Hakekat Lembaga Pendidikan Islam - Ibrahim, Rustam; Sukarno, Sesarian Nur Khoiriyah; Marhenisaputri, Intan; Rahmadani, Eka (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
Islamic education is a systematic effort aimed at developing the potential of human resources based on Islamic values. The essence of Islamic education includes the formation of character, morals, and intellectual and spiritual development in order to form a complete individual (insan kamil). The definition of Islamic education according to Islamic figures reflects a diversity of approaches, from the formation of personality to guidance for living in society. The basis of Islamic education involves the Qur'an, Sunnah, and the thoughts of scholars, with the aim of guiding humans to obey Allah and live in society well. Islamic educational institutions are divided into formal and nonformal, with formal institutions such as Islamic boarding schools, madrasas, and Islamic universities playing a role in the development of religion and science. The function of Islamic education includes the formation of a moral personality, the development of emotional intelligence, and the instillation of social and spiritual values. Thus, Islamic education has a strategic role in facing the challenges of modernization and globalization, while forming a generation that is not only intelligent but also has noble morals. The urgency of Islamic education, especially in early childhood, is very important to form a character that is in accordance with religious teachings, so this education must be carried out continuously throughout life.